A study to investigate the cause of failure of pedestrian bridge Pasir Gudang, Johor - Elliza, Marcellus (2015)
Recently reported numbers of damage occurred to pedestrian footbridge in Malaysia. It had become significantly since there is affected loss in property and may also cause injury to people. On 12 October 2014, a pedestrian footbridge located at Perling – Pasir Gudang Highway was destructed by the wind storm. However wind speed at the nearest meteorological station are not showed any significant value that may damage the pedestrian footbridge. Therefore this study was carried out to investigate the effect of wind to the pedestrian footbridge. Computational Fluid Dynamic has been used in order to examine the effect of wind to structures. The model was examined with different direction of wind speed. From the result it obviously shows that the wind speed may increase suddenly when gust of wind reach to the structure. The interaction between the wind and the structure component might increase the wind speed up to 78% from the north direction. Additionally historical wind speed data at the nearest meteorological station was also examined. Past wind speed also shown that primary wind blow come from North Direction. Repetition of wind speed from same direction can also cause a fatigue failure to the structural component. It can be conclude that the consideration during the design stage are should be properly estimated. The orientation of footbridge may increase the potential of wind induce failure to the structure. Hence the wind speed direction and the interaction between the wind and structure need to be well recognized at design stage in order to reduce the wind risk to pedestrian footbridge component